Riesgos psicosociales en la calidad de vida laboral del personal de planificación del GAD del cantón Sucre - Pazmiño Alvarado, Sandro Paúl (2021)
The present research was carried out in the Planning Department of the GAD in Sucre-Manabí canton, its purpose was to evaluate the psychosocial risks in the quality of work life of the personnel for its subsequent intervention. To identify the risks, a questionnaire proposed by the Ministry of Labor in Ecuador was used, through surveys directed directly to workers, with different dimensions and items to select, techniques such as interviews and checklists were also used to obtain information about the current situation of the company. Subsequently, the identification, measurement and evaluation of the data suitable for the responses of each worker was carried out, weighing them by means of a table according to the instrument used. With this, it was evidenced that in the Planning department the main psychosocial risks within the low-risk classification occurred in the leadership and work organization dimensions, while the medium risk classification occurred in the load and rhythm dimensions of work and recovery, these risks indicate that workers are exposed to potential minimal and moderate impacts, which if not controlled or monitored can present harmful effects on health. To improve the quality of workers life, a psychosocial risk prevention program was proposed, in order to be able to minimize, reduce and correct said risks present in the Planning department.